2004
DOI: 10.1042/bj20031804
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking of the human Wilson protein: the role of the six N-terminal metal-binding sites

Abstract: The Wilson protein (ATP7B) is a copper-transporting CPx-type ATPase defective in the copper toxicity disorder Wilson disease. In hepatocytes, ATP7B delivers copper to apo-ceruloplasmin and mediates the excretion of excess copper into bile. These distinct functions require the protein to localize at two different subcellular compartments. At the trans-Golgi network, ATP7B transports copper for incorporation into apo-ceruloplasmin. When intracellular copper levels are increased, ATP7B traffics to post-Golgi vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(148 citation statements)
references
References 42 publications
9
138
0
1
Order By: Relevance
“…ATP7B with non-functional MBDs (which cannot bind copper) does not traffic in response to copper elevation (32). Residues S340/341 are located within the long loop connecting MBD3 and MBD4 and are not expected to have any effect on copper binding capacity of N-ATP7B, although this remains to be experimentally verified.…”
Section: Discussionmentioning
confidence: 99%
“…ATP7B with non-functional MBDs (which cannot bind copper) does not traffic in response to copper elevation (32). Residues S340/341 are located within the long loop connecting MBD3 and MBD4 and are not expected to have any effect on copper binding capacity of N-ATP7B, although this remains to be experimentally verified.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Plasmid Constructs-To generate a bait construct that encoded the entire N terminus of ATP7B, a 1971-bp fragment that encoded amino acids 1-657 was amplified by PCR using pCMB278 (19) as a template, the forward primer 5Ј-ccccatatgATGCCTGAGCAG-GAGAGACAG-3Ј (hWND30) and the reverse primer 5Ј-gggcagctgC-GACGTGTCCTTTCTGAAGAAGGTGAC-3Ј (hWND8) (NdeI and SalI restriction sites in lowercase boldface type). The resulting PCR product was cloned into the NdeI/SalI restriction sites of the GAL4 DNA binding domain (BD) vector pAS2-1 (Clontech) to create plasmid pAS2-1/ATP7B-N (pSLB10).…”
Section: Methodsmentioning
confidence: 99%
“…To create plasmid constructs that encoded mutated or deleted ATP7B N termini as baits, PCR was carried out using the forward primer hWND30, the reverse primer hWND8, and the following plasmids as templates (19): pCMB398, which encoded ATP7B with both cysteines within the CXXC motif of all six of the metal binding domains mutated to serine (i.e. SXXS); pCMB404, which encoded ATP7B with MBS 1-5 deleted leaving only MBS 6; and pCMB405, which encoded ATP7B with MBS 4 -6 deleted leaving MBS 1-3 intact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational studies performed to address the role of the N-WLNP have found that, generally, the domains closest to the membrane seem to be the most important both for the ultimate incorporation of copper into Fet3 in yeast complementation assays and in the copper-dependent translocation of WLNP from the vesicular to the cytosolic membrane (23)(24)(25). However, the mechanism by which these domains acquire copper and then transport it across the vesicular membrane is unknown.…”
mentioning
confidence: 99%